One-pot synthesis of palm oil-based polyester polyol for production of biodegradable and biocompatible polyurethane - Yeoh, F.H.; Lee, Choy Sin; Kang, Yew Beng; Wong, S.F.; Cheng, Sit Foon (Wiley, 2018)
Palm oil-based polyester polyol was synthesized by reacting epoxidized palm olein with malonic acid under a convenient one-pot synthesis method. The optimum reaction time, temperature, and functionality molar ratio were determined. The optimal polyol consisted of hydroxyl and acid values of 98.19 and 1.44 mg KOH/g sample, 95% conversion of epoxides and Mn of 5201 Da; and the chemical structure was elucidated by Fourier transform infrared, Carbon-13 nuclear magnetic resonance (NMR), and 1H-NMR. The polyol was appeared as light-yellowish liquid with cloud and pour points of 12 and 10 °C and reacted with isophorone diisocyanate to produce polyurethane with interconnected pores ranged 35–2165 μm, porosity ranged 89–90%, tensile strength ranged 59–78 kPa, and compression stress ranged 48–55 kPa. The polyurethanes showed 120–260% water-uptake and controlled mass loss (1.6–15.3%) after 28 days of enzymatic degradation. PU 1 demonstrated slight cytotoxicity with cell proliferation and adhesion observed after 24 h incubation, demonstrated its potential as biomaterial for biomedical applications.